2015
DOI: 10.1103/physrevb.92.100304
|View full text |Cite
|
Sign up to set email alerts
|

Space-time gradient metasurfaces

Abstract: Metasurfaces characterized by a transverse gradient of local impedance have recently opened exciting directions for light manipulation at the nanoscale. Here we add a temporal gradient to the picture, showing that spatio-temporal variations over a surface may largely extend the degree of light manipulation in metasurfaces, and break several of their constraints associated to symmetries. As an example, we synthesize a non-reciprocal classical analogue to electromagnetic induced transparency, opening a narrow wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
274
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 372 publications
(278 citation statements)
references
References 44 publications
1
274
3
Order By: Relevance
“…[ 167 ] Beside the spatial gradient, a transverse temporal gradient can also be taken into account to break the reciprocity symmetry, which shows important application in nonreciprocal devices, such as optical diode. [ 168 ] More comprehensively, such concept of wave control has been applied to diverse disciplines for wave-matter interactions, such as acoustics, [ 169,170 ] thermal physics, [ 171,172 ] etc.…”
Section: Other Applicationsmentioning
confidence: 99%
“…[ 167 ] Beside the spatial gradient, a transverse temporal gradient can also be taken into account to break the reciprocity symmetry, which shows important application in nonreciprocal devices, such as optical diode. [ 168 ] More comprehensively, such concept of wave control has been applied to diverse disciplines for wave-matter interactions, such as acoustics, [ 169,170 ] thermal physics, [ 171,172 ] etc.…”
Section: Other Applicationsmentioning
confidence: 99%
“…The strategy introduced in this paper can be considered as a temporal analogue of the typical space-gradient metasurface [22,23, 24,25,27]. Thus, by combining both strategies one could design an all-optical space-time gradient metasurface to break the geometrical and temporal symmetry on-chip [38,39], design ultrafast temporal holograms, and control the directivity of emission using an optical gate signal [40,41].In summary, we have demonstrated that a metasurface geometry is uniquely suited to achieving large nonlinear refraction. We have shown that a metasurface may exhibit an extremely large intensitydependent refractive index if an epsilon-near-zero medium is incorporated into the design.…”
mentioning
confidence: 99%
“…The concept is based on imparting a suitable form of momentum biasing that breaks time-reversal symmetry, achieved with mechanical motion or with spatiotemporal modulation (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). In this paper, for the first time to our knowledge, we apply these concepts to emitting/absorbing systems, showing that it is possible to realize magnetic-free nonreciprocal structures that can emit without absorbing from the same direction over a broad frequency range.…”
mentioning
confidence: 99%